Analysis of the effect of infection control strategy in preventing and controlling infectious endophthalmitis after cataract surgery - Na Liu; Xiao Yang; Dongyan Guo; Qi Wang; Jianhua Zhang; Xiaoming Wang (BMC Ophthalmology)
Abstract Background The goals of this study was to analyze and explore the effect of comprehensive sensory control strategy on prevention and control of infectious endophthalmitis after cataract surgery. Methods From January 2012 to December 2023, a study of patients with infectious endophthalmitis after cataract surgery was conducted in a hospital. Perioperative infection prevention measures include topical eye drops, lacrimal irrigation, povidone iodine disinfection of conjunctival sac, etc. After in-depth investigation and analysis of the reasons for the increase in the incidence of endophthalmitis for three times, a series of effective prevention and control measures were proposed for the root causes of the problems, including optimizing the key link system, implementing closed-loop management of sensory control measures, designing personalized children’s surgery plan, strengthening perioperative treatment, comprehensively monitoring the operating room clean system, strengthening the cleaning and disinfection treatment between consecutive operations to ensure the safety of the operating environment, etc. Results From January 2012 to December 2023, a total of 134,045 cataract operations were performed, of which 26 cases were infected at the surgical site, with an infection rate of 0.019%. According to the specific infection characteristics of each period, corresponding prevention and control measures were formulated and implemented, which significantly reduced the incidence of endophthalmitis (P < 0.01). In 2012, 2016 and 2020, the incidence of endophthalmitis was 0.057%, 0.048% and 0.029%, respectively, showing a linear decreasing trend, which was statistically significant (X 2  = 19.793, P ≤ 0.01). Conclusions By analyzing the characteristics of infectious endophthalmitis in different periods, the main causes can be inferred, and the prevention and control measures can be explored to effectively reduce the incidence of infectious endophthalmitis after cataract surgery.